Key factor keberhasilan transfer of knowledge Pendidikan Agama Islam dalam perspektif keterbukaan Informasi - Anwar Sholihin (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
The education process can be formulated as a process of humanization, meaning that it develops a sense of humanity that has a sense of moral and religious values, which takes place both in the personal, family, community and national, present and future environment. From the results of the discussion concluded: 1) The presence of self-understanding of critical, dialogical and transformative education is the key to facilitating the emergence of a balanced and mature Islamic sense in the modern world. 2) so that the learning process of Islamic education is truly transformative, each theological reflection incorporates an empirical dimension with critical involvement to facilitate a smart and meaningful perspective. 3) to assess the validity of information on the internet, special competencies are needed, which have not been taught in formal education. the development of new skills to build a 'digital learning' framework is an important part of the process of re-establishing a transformative educational culture. 4) Transformative learning is not just transforming knowledge or information to students, but more important is the transformation of mindset, thought patterns and methodology. In this way students will process science or information that is obtained critically, reflective, and openly not only to look for the right, but the most correct.